La morte nel libro della Sapienza - Zieliński, Marcin (The Biblical Annals, 2017)
The article analyzes the theme of death in the book of Wisdom, with particular attention to the relationship between Wisdom and death. After a general introduction to the theme of death and the concept of “second death”, the author analyzes the marriage metaphor, which occupies an important place in the second part of the book. The author proceeds with the analysis of vocabulary and images related to the marriage metaphor. Searching for a possible counter-metaphor, he indicates the image from Wis 1,16, where the relation of the wicked with death is described as a tragic denial of the ideals presented in Wis 8,16,17-18. The elements that link the two images and at the same time make them totally different are indicated. Pseudo-Solomon emphasizes the beauty of the relationship with Wisdom on the one hand and the drama of the sinners on the other, to conclude that the wicked, seeking to enter into a friendly relationship with death, get exactly the opposite of what the sage receives from the Wisdom in the II part of the Book of Wisdom.